Памяти доктора технических наук, профессора Шишова Валентина Павловича - Муховатый, А. А.; Ревякина, О. А.; Ткач, П. Н. (НТУ "ХПИ", 2014)
В статье рассказывается о творческом пути известного ученого-теоретика, посвятившего себя созданию новых видов передач зацеплением, доктора технических наук, профессора Шишова Валентина Павловича. Подробно освещены его основные достижение в области теории и практики исследования передач зацеплением.

The article discusses the creative path of the famous scientist and theoretician, who devoted himself to the creation of new types of gear engagement, doctor of technical sciences, professor Shishov Valentin Pavlovich. Details covered his main achievement in the field of theory and practice of gearings research.
Memoirs on doctor of technical sciences, professor Valentin Pavlovich Shishov
Keywords: зубчатая передача; зацепление Новикова; синтез; gear; Novikov mesh; synthesis